Paradigma Biblika, Teologis dan Ontologis Mengenai Perintisan Jemaat - Mawikere, Marde Christian Stenly; Hura, Sudiria; Legi, Hendrik (Sekolah Tinggi Agama Kristen Diaspora Wamena, 2024)
This research explores the fundamental differences between the concept of Church Planting and general approaches in contemporary church growth. The article highlights that church planting is driven by strong theological principles, putting church ontology as the cornerstone. It is presented that hermeneutics must precede methodology, and theology must precede anthropology. Readers are invited to explore the deeper and scholarly dimensions of Church Planting. Church planting involves planting congregations and emphasizing the ontological dimension closely related to evangelism, in accordance with biblical teachings. Qualitative research with a hermeneutic approach and theological studies reveals that the ontology of church planting is derived from the Bible, involving a proper understanding of church doctrine. This article makes an important contribution to the scholarly discourse on church planting, discussing theological, ontological, and finally methodological aspects as implications. This article makes an important contribution to the scholarly discourse on church planting, discussing theological, ontological, and finally methodological aspects as implications. The novelty of this study lies in an approach that emphasizes a deeper understanding of the concept of church planting, distinguishes it from the general approach to church growth, and highlights the urgency of church ontology as the main foundation in church planting, which then has implications in the methodology and practice of church evangelism.AbstrakPenelitian ini mengeksplorasi perbedaan fundamental antara konsep Perintisan Jemaat dan pendekatan umum dalam pertumbuhan gereja kontemporer.. Artikel menyoroti bahwa perintisan jemaat didorong oleh prinsip-prinsip teologi yang kuat, mengedepankan ontologi gereja sebagai landasan utama. Disajikan bahwa hermeneutik harus mendahului metodologi, dan teologi harus mendahului antropologi. Pembaca diundang untuk menjelajahi dimensi lebih mendalam dan ilmiah terkait Perintisan Jemaat. Perintisan jemaat melibatkan upaya menanam jemaat dan menekankan dimensi ontologis terkait erat dengan penginjilan, sesuai dengan ajaran Alkitab. Penelitian kualitatif dengan pendekatan hermeneutik dan kajian teologis mengungkapkan bahwa ontologi perintisan jemaat bersumber dari Alkitab, melibatkan pemahaman doktrin gereja yang tepat. Artikel ini memberikan kontribusi penting dalam wacana ilmiah mengenai perintisan jemaat, membahas aspek teologis, ontologis, dan terakhir aspek metodologis sebagai implikasinya. Artikel ini memberikan kontribusi penting dalam wacana ilmiah mengenai perintisan jemaat, membahas aspek teologis, ontologis, dan terakhir aspek metodologis sebagai implikasinya. Kebaharuan dari penelitian ini terletak pada pendekatan yang menekankan pemahaman yang lebih dalam terhadap konsep perintisan jemaat, membedakannya dari pendekatan umum dalam pertumbuhan gereja, serta menyoroti urgensi ontologi gereja sebagai landasan utama dalam perintisan jemaat, yang kemudian membawa implikasi dalam metodologi dan praktik penginjilan gereja.